A modelling approach for allocating land-use in space to maximise social welfare - exemplified on the problem of wind power generation - Martin Drechsler; Cornelia Ohl; Jürgen Meyerhoff; Marcus Eichhorn; Jan Monsees (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
Land-use conflicts arise if land is scarce, land-use types are mutually exclusive, and vary in their effects with regard to more than one incongruent policy objective. If these effects depend on the spatial location of the land-use measures the conflict can be mediated through an appropriate spatial allocation of land use. An example of this conflict is the welfare-optimal allocation of wind turbines (WT) in a region in order to achieve a given energy target at least social costs. The energy target is motivated by the fact that wind power production is associated with relatively low CO2 emissions and is currently the most efficient source of renewable energy supply. However, it is associated with social costs which comprise energy production costs as well as external costs caused by harmful impacts on humans and biodiversity. We present a modelling approach that combines spatially explicit ecological-economic modelling and choice experiments to determine the welfare-optimal spatial allocation of WT in Western Saxony, Germany. We show that external costs are significant. The welfare-optimal sites are therefore not those with the highest energy output (i.e., lowest production costs). However, they show lower external costs than the most productive sites. A sensitivity analysis reveals that the external costs represent about seven percent of the total costs (production costs plus external costs). Increasing the energy production target increases both production and external costs. The absolute (percentage) increase of production costs is higher (lower) than that of external costs.
Keywords: Q42; Q51; Q57; 330; choice experiment; ecological-economic modelling; externality; spatial allocation; welfare-optimal; wind power; Windenergieanlage; Standortwahl; Bodennutzung; Allokation; Soziale Wohlfahrtsfunktion; Windenergie; Biodiversität; Soziale Kosten; Theorie